Integrated surface geophysical approach to locate a karst conduit: a case study from Royal Spring Basin, Kentucky, USA (Journal of Nepal Geological Society, 2016)
Groundwater flow in karst terrains is difficult to map because it can be concentrated through conduits that do not necessarily coincide with the surface features. We applied electrical resistivity (ER) and self-potential (SP) techniques at three sites to locate an inferred trunk conduit feeding a major spring in the Inner Bluegrass region of Kentucky (USA). Royal Spring is the primary water supply for the city of Georgetown; the upper part of its basin coincides with the Cane Run watershed. ER profiles (972 m total length) were measured using a dipole–dipole electrode configuration with 2- to 3-m spacing. SP measurements were taken along those ER lines and an additional test profile (230 m) using one stationary reference electrode and another roving electrode at a fixed interval. The SP technique has been used by many researchers to detect the electro kinetic potential generated by groundwater flow. The low resistivity of water in the conduit, as compared to the high background resistivity of limestone bedrock, was the ER exploration target. A negative SP anomaly corresponded to a low ER anomaly for most of the profiles, but a few are not comparable. Although SP data collected over multiple days along the test profile differed significantly, they showed similar trends. Field drift in SP data was found to be highly sensitive to temperature changes during the time of measurement. Although the overall trends of the final SP profiles for different dates were similar, the SP magnitudes varied with the amount of precipitation and the average soil temperature. The low-resistivity anomalies in the 2D inverted sections and corresponding negative SP anomalies at two sites (Berea Road and Kentucky Horse Park) encountered water-filled conduits, although mudfilled voids encountered during drilling at University of Kentucky Agricultural Research Farm sites suggest that these may be tributary conduits rather than the trunk conduit.